FYR Macedonia : Decentralization Status Report - World Bank (Washington, DC, 2013)
To institutionalize the decentralization elements of the peace settlement in Macedonia, the Framework Agreement calls for specific changes in the Constitution, and three specific items of legislation: a new law on local governments specifying the functions they are to assume, a local finance law specifying how these functions are to be financed, and, a law revising the boundaries of local governments, on the basis of a new census. While the Constitutional amendments have been approved, progress on the rest of the legislative agenda has proceeded slowly. The census on which the territorial reform was to be based has only recently been completed. The local government law has been approved, but requires extensive subsidiary legislation before it can be implemented. The new finance law is only now in the drafting process. The next local elections are scheduled for 2004, thus a considerable amount of work will be required to ensure that the impact of decentralization will be perceptible to the electorate by that time. This paper is directed at two audiences: the first is the Government, which is now in the process of drafting detailed legislation on territorial reform, local finance, and the decentralization of specific sectors. For this audience, the report lays out some of the issues that will need to be addressed in the course of implementing the decentralization provisions of the Framework Agreement; the second is the World Bank, the European Union (EU) special representative, the U.S. Ambassador, and other members of the donor community. For this audience, the report is intended to describe the present status of the decentralization process, and suggest a strategy for assisting the Government in this sequence of reforms. It reviews the existing legal structure, the expenditure assignment, particularly on education, social protection, and health care, and that of public utilities, as well as the revenue assignment through its municipal taxation, and overall fiscal performance. The report then examines the decentralization framework agreement, and the new legislation being, or to be adopted regarding the local self government law, in particular on social sectors, and proposed changes on municipal competencies. Within the action plan, the Government's current operational program for decentralization of power 2003-04 is presented, outlining the territorial reform which specifies that new municipal boundaries will be defined on the basis of a new census. Regarding finance, under the International Monetary Fund (IMF) report's strategy, municipalities would later assume responsibility for some assets, and related maintenance costs during the subsequent phase of decentralization.